An optimization model for the design of network arch bridges. (1st July 2016) - Bruno, D.; Lonetti, P.; Pascuzzo, A.
Highlights: An iterative optimization algorithm based on a three-step procedure is implemented. The initial configuration is determined avoiding relaxation effects in the hangers. A FE approach coupled with OMs is utilized to derive the design configuration. The design procedure evaluates the global minimum in the required material quantity. Numerical comparisons verify convergence and reliability of the design procedure. Abstract: A new design methodology, which evaluates the optimum configuration of network arch bridge schemes is proposed. A three-step optimization algorithm is implemented in a FE model, with the purpose to evaluate the bridge optimum configuration, involving the lowest material quantity and the best strength performance level in all structural members of the bridge. The stability and the efficiency of the formulation were verified with respect to several bridge configurations ranging from small to large spans. Moreover, parametric results are presented to investigate the interaction between cable-system, girder and arch, giving rise to specific analyses useful for design purposes.